K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 7 2019

Ta có :

\(\left|x-2\right|+\left|x-5\right|=\left|x-2\right|+\left|5-x\right|\ge\left|x-2+5-x\right|=3\)

Dấu "=" xảy ra \(\Leftrightarrow\) \(\left(x-2\right)\left(5-x\right)\ge0\)

\(\Leftrightarrow\)\(2\le x\le5\)

hoặc \(2\ge x\ge5\)( Vô lý)

Vậy \(2\le x\le5\)là giá trị thỏa mãn \(\left|x-2\right|+\left|x-5\right|=3\)

4 tháng 1 2019

2(x - 7) - 3(x + 8) = 5

=> 2x - 14 - 3x - 24 = 5

=> -x - 38 = 5

=> -x = 5 + 38

=> -x = 43

=> x = -43

4 tháng 1 2019

=>2x -14 -3x - 24 =5

=>  x = -43

2 tháng 7 2018

(x-3)(x+5)=(x+3)(x-2)

<=>x2+5x-3x-15=x2-2x+3x-6

<=>x2+2x-15=x2+x-6

<=>x2+2x-15-(x2+x-6)=0

<=>x2+2x-15-x2-x+6=0

<=>x-9=0

<=>x=9

2 tháng 7 2018

\(\left(x-3\right)\left(x+5\right)=\left(x+3\right)\left(x-2\right)\)

\(x^2+5x-3x-15=x^2-2x+3x-6\)

\(x^2+5x-3x-x^2+2x-3x=15-6\)

\(x=9\)

29 tháng 1 2022

minh camon

8 tháng 12 2021

\(\dfrac{2x^3+5 -x^3-4}{x^2-x+1}=\dfrac{x^3+1 }{x+1}\)

8 tháng 12 2021

\(\dfrac{2x^3+5-x^3-4}{x^2-x+1}\) = \(\dfrac{x^3-1}{x^2-x+1}\)

11 tháng 4 2022

\(H\left(x\right)=\left(x-3\right)\left(x^2+5\right)\)

\(\Rightarrow H\left(x\right)=x^3+5x-3x^2-15\)

11 tháng 4 2022

H(x)=(x−3)(x2+5)H(x)=(x−3)(x2+5)

⇒H(x)=x3+5x−3x2-15

Dây nha bạn

18 tháng 10 2021

\(5^{x+2}-5^x=3.10^3\)

\(\Rightarrow5^x\left(5^2-1\right)=3000\)

\(\Rightarrow5^x.24=3000\Rightarrow5^x=125=5^3\)

\(\Rightarrow x=3\)

18 tháng 10 2021

\(5^{x+2}-5^x=3\cdot10^3\)

\(\Leftrightarrow5^x\cdot24=3000\)

\(\Leftrightarrow x=3\)

25 tháng 9 2019

a) ( x + 2 ) ( x + 3 ) - ( x - 2 ) ( x + 5 ) = 0

     x2 + 3x + 2x + 6 - x2 + 5x - 2x - 10 = 0

     8x - 4                                              = 0 

    8x                                                    = 0 + 4

     8x                                                  = 4

       x                                                  = 4 : 8 

       x                                                 = 1/2

      

25 tháng 9 2019

b) 2x ( x -5 ) - x ( 3 + 2x ) = 26

 2x2 - 10x - 3x - 2x2          = 26

-13x                                  = 26

x                                       = 26 : (-13)

x                                      = -2 

30 tháng 4 2018

\(2^5.x-2^3.x+x=\left(7^5:7^5\right).2\)

\(\Rightarrow32.x-8.x+x=1.2\)

\(\Rightarrow\left(32-8+1\right).x=2\)

\(\Rightarrow25.x=2\)

\(\Rightarrow x=2:25\)

\(\Rightarrow x=\frac{2}{25}\)

Vậy \(x=\frac{2}{25}\)